The institutionalization of practice: a processual perspective on value co-creation - Patora-Wysocka, Zofia (Economics and Business Review, 2016)
Abstract : Drawing on the processual perspective in management this article explores the process of the institutionalization of new practice in the context of value co-creation. The Service-Dominant logic perspective places the notion of value creation in the interaction between an organization and its customers. Therefore the contemporary research stream shows a bias towards the notion of a customer as a crucial contributor and beneficiary in the value creation process [Vargo and Lusch 2006a, 2008]. Following recent calls for research with a holistic approach it may be assumed that there is an underdeveloped processual perspective on value co-creation that offers a cognitive framework of routines and activities performed on an everyday basis within the Giddensian structuration theory. Using the Giddensian theory value co-creation can be perceived as a platform for the adoption of new practices. The purpose of the article is to determine the role of value co-creation processes in the context of initiating and institutionalizing of new practice in an organization. A comparative case study was carried out which illustrates the thesis that spontaneous actions form an important category of initiating change within the everyday use of value co-creation.